Gender Differences in ESL Learners’ Mastery Of Prepositions: Implications for Designing Instructional Materials - Avila, Kheneth Sherwin; Ravago, Joan; Torres, Joel; Tanpoco, Manuel (International Journal of Language and Literary Studies, 2025)
Learning prepositions is a challenging task for ESL learners, and previous studies have focused on assessing mastery levels and identifying difficulties. This mixed methods research examines the correlation between gender and mastery levels in using the prepositions at, for, in, on, to, and with, as well as frequently missed questions and problems in their usage among 26 Grade 12 senior high school students. The quantitative analysis involved a t-test to compare the performance of male and female participants. The results indicate that both males and females achieved a weak mastery level in using prepositions. However, among the 11 frequently missed questions, male participants exhibited a higher error percentage than female participants. Additionally, both genders encountered similar problems related to preposition use, which were categorized into five themes: (1) unfamiliarity with the rules, (2) confusion due to sentence meaning, (3) context-based sentence construction, (4) interference, and (5) sound dependence. These findings suggest that instructional materials for preposition use need not be gender-specific but rather require a corpus-based approach and the inclusion of contextualized examples. However, the generalizability of these results is limited due to the small sample size, highlighting the need for further research with a larger and more diverse participant pool.